Rapid THz time-of-flight imaging on single layer graphene for conductivity assessment - Kim, Young Chul; Yim, Jong Hyuk; Khan, Abbas Ahmad; Kim, Jangsun; Ahn, Yeong Hwan (Infrared Physics and Technology, 2024)
The assessment of the electrical conductivity of single-layer graphene (SLG) on flexible substrates is pivotal for the advancement of next-generation electronic devices. In this study, we introduce a novel approach utilizing a rapid terahertz time-of-flight (THz-ToF) imaging technique to nondestructively evaluate the conductivity of SLG films transferred onto plastic substrates. Operating at a pixel scan rate of 100 Hz, our method significantly enhances the imaging contrast by exclusively focusing on the surface with SLG, which is demonstrated by a two-fold increase in contrast over continuous wave imaging results. The employment of an iron-doped antenna has been instrumental in obtaining high-fidelity cross-sectional amplitude images of the graphene layers, a feature essential for the inspection of thin and flexible materials. Furthermore, THz-ToF imaging allows us to map the graphene layer even when it is enclosed by an insulating material, enabling the 3D mapping of conductive layers in multilayered structures. We obtained conductivity mapping of SLG on the plastic substrate using Tinkham formula. The superior performance of this method promises a significant leap forward in the rapid and accurate assessment of conductive films, with profound implications for the development of flexible electronics and bendable displays.
Keywords: Conductivity assessment; Electrical conductivity; Flexible substrate; Graphene layers; Plastic substrates; Single layer; Tera Hertz; THz imaging; Time-of flight; Time-of-flight imaging; Conductivity assessment; Graphene; THz imaging; Time-of-flight